Medical Jousting: Going for the kill! - Dr.Fuad Ahmed Khan Niazi (Journal of Rawalpindi Medical College, 2023)
He stood determined, focused on the target, his grip on the lance tightening just the right amount, aimed toward the enemy warrior with the precision of an excellent marksman. All set to joust, he leaped gallantly toward his opponent. So sure, of himself, he wanted the win and victorious he was. The triumphant doctor, our knight in shining armor stood tall beside his trophy. Was he dead? he didn’t really care; he had won. The crowd cheered for him as he waived proudly and then stooped forward to reach for the helmet; he wanted to see his face! Who was he? Prince Covid, Sir Typhoid or the Lord Dengue? He was dying and a bare murmur could be heard over his last breath: “I am your brother!!” Through the evolution of medicine, from medieval times to the modern day, medical jousting has kept haunting us. It is essentially a term meant to describe the use of derogatory comments or gestures in front of a patient or attendant, concerning previous medical care provided by a fellow healthcare professional, without complete or accurate knowledge about real facts.1 “I do not even consider her a doctor; who told you to get operated by her?” A comment which might have touched a sensitive wire somewhere in your emotional memory, is an actual recollection of what I myself overheard once. Or, maybe, remembering someone who used to grin, rather peculiarly, when a patient mentioned another colleague’s name, just enough to create sufficient doubt in their minds, will jolt up some sensitive recollections. Although, this unfortunate practice can be unintentional, sadly, it is more often than not, intentional. It emanates from the deep-rooted instinct of us humans to survive and feel jealous or intimidated by an equal or someone who shares the same goals and targets. This fear leads to insecurity and creates competition out of friends. These complexes tend to flourish more in private healthcare sector where money and high patient turnover matters. However, it is not uncommon even in public sector, where fame and career are the ultimate objective. Unintentional jousting may happen when someone tries to project oneself so much that eventually ends up denigrating others. For example: “It’s good that you have come to me; all your problems will now be cured, at last.” Medical Jousting may also be due to a lack of knowledge about other specialties in the context of multidisciplinary patient care or, it may just be a defensive mechanism to bail out of a complication; why not just blame it on someone else!!2 A far less common, albeit, a much more dangerous way is to write incriminating statements against other health professionals. “This complication has developed because of the stubborn attitude of the anesthetist who kept refusing to intubate our patient without any justifiable reason.” In these times of medical litigation, such notes can be suicidal as well as being murderous. More recently, the most disparaging and scornful form of jousting has been through the use of social media, given its endless scope and lethal repercussions.3,4 In trying to develop an understanding of the phenomenon of medical jousting, it needs to be remembered that it is the right of the patient and their families to know the truth. However, truth needs to be discovered through a proper trail of medical record and a well-intended chat with the previous attending doctor. Also, the truth needs to be delivered in its entirety in a neutral manner without compromising the integrity, or safety, of a fellow professional. It also needs to be emphasized, that, any medical error or unethical behavior should be reported through proper channels to relevant bodies with the motive to ensure benefit to the patient, and, improvement and development of the involved colleague. Under no circumstances should such discussion be carried out in front of patients, their attendants or any unrelated person.5 Medical jousting is a real-life problem that genuinely exists and threatens our profession. In a study it was shown that among all the comments that were made about another doctor during patient consultation, 67% were accusing or critical while only 29% were supportive.6 This unnecessary evil, encompassing our ‘noble profession,’ can result in, not only the loss of confidence and faith in the medical professionals, but also, respect in the eyes of the common man. This may potentiate a surge in an already alarming tendency of violence, among a certain segment of our population, against hospitals and healthcare workers. It can, however, be avoided with the collective effort of all the professionals. Jousting should be categorically denounced as professionally unethical and efforts for its elimination should be encouraged at all levels. “Speak truth in such a way that it should be pleasing to others. Never speak truth which is unpleasant to others. Never speak untruth which might be pleasant.” (Anonymous)